SCORING SYSTEM APPLICATION IN MANAGEMENT CHOICES AND PROGNOSIS OF THE PROCEDURE IN PATIENT WITH RISK OF AIRWAY OBSTRUCTION: ARTICLE REVIEW - Asriantin, Isna; Suryantarini, Ni Wayan Puspa Wijaya (Mandala Of Health, 2025)
Airway obstruction is a life-threatening condition that requires prompt recognition and management to prevent morbidity and mortality. Intubation remains the gold standard for securing the airway; however, failed attempts are common and may delay other life-saving interventions. To improve decision-making in selecting appropriate procedures and predicting outcomes, various scoring systems have been developed. This article aims to review the application of scoring systems in management choices and prognosis of patients with risk of airway obstruction. This study employed a systematic literature review by searching PubMed, ScienceDirect, and ProQuest databases using the keywords “scoring system,” “airway obstruction,” “difficulty,” and “management prediction.” Eligible studies included original research and case reports published in English or Indonesian between 2020 and 2025, with complete full-text availability. Eight relevant articles were identified and analyzed. The findings suggest that proper application of validated scoring systems may reduce the incidence of failed intubation, guide elective tracheostomy decisions, and improve prognosis in patients at risk of airway obstruction. Nevertheless, inappropriate or excessive use may lead to unnecessary procedures and complications. Further research is needed to validate these tools across diverse populations and to develop simplified scoring models with higher sensitivity and specificity.